Kajian bakteri proteolitik yang diisolasi dari tubuh lalat hijau (Chrysomya megacephala) - Hidayati, Ernin; Nurhimaya, Ika; Mahdi, Nisful; Sarkono, Sarkono (Jurnal Biologi Udayana; Vol 26 No 2 (2022): JURNAL BIOLOGI UDAYANA, 2022)
Blowfly ( Chrysomya megacephala ) is an insect that has an important ecological role,  one of which is as a decomposer. Blowfly is often found around food and garbage, especially those protein-rich. The perch of the blowfly on foods needs to be aware because it causes the material to spoil or stale faster. It is suspected that the bacteria present in the fly's body play a role in the material decomposition process. This research aims to study proteolytic bacteria isolated from the body of the blowfly. The sample of blowfly was taken from the dumping site at Kebon Kongok, West Lombok, Indonesia. The samples were placed into Brain Heart Infusion Broth. Bacteria from the body of the blowfly were isolated using Nutrient Agar. The proteolytic activity of the bacterial isolates was detected from the formation of a clear zone on the Skim Milk Agar medium using the spot and well diffusion method. The isolates were characterized by using Gram staining and a series of biochemical tests. There were four isolates of proteolytic bacteria found in the body of the blowfly, namely LH1, LH2, LH3, and LH4. The LH2 showed the best catalytic activity with an average clear zone diameter of 25.5 mm after 24 hours of incubation at 37 o C. LH2 is a Gram negative, rod-shaped and short chain, motile, and aerobic. Based on the biochemical test, LH2 is able to utilize several types of sugars such as arabinose, sucrose, maltose, and mannitol, able to oxidize the amino acid tryptophan, and able to convert urea into ammonia. The results of this study provide information that LH2 contributes to the decomposition process and also potential as a pathogen.